Delayed leukoencephalopathy from suspected polymer embolism after neuroendovascular procedures. Issue 4 (August 2021) - Mellemkjær, Thomas; Chandra, Ronil V; Speiser, Lasse; Ulhøi, Benedicte P; Simonsen, Claus Z
As the neurointervention field grows, a new side effect emerges. Delayed leukoencephalopathy (DL) is believed to be an inflammatory or allergic reaction to polymer material that is shed from catheters during endovascular procedures. We present four cases of DL after aneurysm treatment in two patients, endovascular stroke treatment and diagnostic arteriography. We present our diagnostic process, including biopsy results in two patients, our anti-inflammatory treatment and outcomes together with a review of the literature. In our series, prognosis was variable with ongoing seizures in two patients. Our literature review reveals that asymptomatic shedding of polymer material is common, occurring in a third of endovascular stroke procedures, whereas symptomatic DL occurs in <0.5% of therapeutic neuroendovascular procedures. Clinicians should be aware of this rare complication, and oral glucocorticoids seem to be a reasonable first-line treatment strategy.